1986
DOI: 10.1038/ki.1986.249
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneovenous shunt in the management of the hepatorenal syndrome

Abstract: The hepatorenal syndrome (HRS) is a terminal complication of severe liver disease associated with a mortality of 80 to 90%. Although the renal functional abnormalities in the HRS suggest prerenal azotemia, volume expansion with saline, albumin or ascitic fluid rarely results in reversal of the HRS because fluid redistributes from the vascular space. Since the peritoneovenous (PV) shunt causes sustained central volume expansion, it has been advocated for the treatment of the HRS. We prospectively compared the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…Forty-four patients responded to therapy and HRS recurred in only nine. These findings contrast sharply with those of 7 studies in patients with type-1 HRS not receiving specific treatment or treated with plasma volume expansion alone or associated with vasodilators (dopamine) or octreotride or with peritoneo-venous shunting [18,19,59,72,77,79,80]. Reversal of HRS was observed in only 4 out of the 137 patients (2.9%) included in these studies.…”
Section: Vasoconstrictors and Albumincontrasting
confidence: 83%
“…Forty-four patients responded to therapy and HRS recurred in only nine. These findings contrast sharply with those of 7 studies in patients with type-1 HRS not receiving specific treatment or treated with plasma volume expansion alone or associated with vasodilators (dopamine) or octreotride or with peritoneo-venous shunting [18,19,59,72,77,79,80]. Reversal of HRS was observed in only 4 out of the 137 patients (2.9%) included in these studies.…”
Section: Vasoconstrictors and Albumincontrasting
confidence: 83%
“…Application of a peritoneo-venous shunt (PVS), often useful in improving renal function in cir rhotics with ascites and decreasing pressure in inferior vena cava, is not able to signifi cantly prolong life in patients with HRS [158],…”
Section: Increase In Intra-peritoneal Pressurementioning
confidence: 99%
“…Indeed, two controlled studies have shown only a slight improvement in renal function following peritoneovenous shunting in these patients. 31,32 Moreover, shunt-induced peritoneal alterations (i.e. shunt-related fibrous adhesions and even 'cocoon' formation) can make subsequent liver transplantation difficult.…”
Section: Peritoneovenous Shuntsmentioning
confidence: 99%